2015
DOI: 10.1080/16184742.2014.998695
|View full text |Cite
|
Sign up to set email alerts
|

The Olympic Games and raising sport participation: a systematic review of evidence and an interrogation of policy for a demonstration effect

Abstract: Research questions: Can a demonstration effect, whereby people are inspired by elite sport, sports people and events to actively participate themselves, be harnessed from an Olympic Games to influence sport participation? Did London 2012 sport participation legacy policy draw on evidence about a demonstration effect, and was a legacy delivered? Research methods: A worldwide systematic review of English language evidence returned 1778 sources iteratively reduced by the author panel, on advice from an internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
206
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(229 citation statements)
references
References 31 publications
8
206
1
5
Order By: Relevance
“…5 Major multi-sport games have failed to achieve an inherent, substantial PA legacy. 6 Measures that could help address this lack of legacy include (1) producing a clear strategy to increase participation and (2) de-emphasising the sporting element and promoting PA more generally (for example, walking) rather than simply the sport being played. 7 8 Golf can provide a novel and suitable narrative to provide a link between sport, walking and potential health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…5 Major multi-sport games have failed to achieve an inherent, substantial PA legacy. 6 Measures that could help address this lack of legacy include (1) producing a clear strategy to increase participation and (2) de-emphasising the sporting element and promoting PA more generally (for example, walking) rather than simply the sport being played. 7 8 Golf can provide a novel and suitable narrative to provide a link between sport, walking and potential health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings (Weed et al 2015) have shown that demonstration effect will result in increasing the frequency of participation of people who are already engaged in sport/physical activity. Also, the demonstration effect would not bring new participants to start in activity.…”
Section: Conclusion and London 2012 Sport Policymentioning
confidence: 99%
“…While summarizing former studies, Weed et al (2015) presented some conclusions on the processes of demonstration effect. It seems that demonstration effect increased participation frequency among people that were already engaged in physical activity, but had no influence on those with no previous intention to engage in sport or physical activity.…”
Section: Demonstration Effect and Sport Participationmentioning
confidence: 99%
See 2 more Smart Citations